Structural Transformation and Rural Change Revisited : Challenges for Late Developing Countries in a Globalizing World - Losch, Bruno; Fréguin-Gresh, Sandrine; White, Eric Thomas (Washington, DC: World Bank, 2013)
Structural transformation and rural change revisited challenges for a late developing country in a Globalizing World is an extremely thorough and important contribution to this renewal of structural economics. It significantly improves our understanding of rural economies and structural transformation, and it could not be timelier. With duration of five years (2006-2010), its objective was to analyze the processes of liberalization and economic integration and their impacts on agriculture and the rural sector of developing countries. It also aimed to illustrate the situation of rural economies in terms of income, diversification, and overall transformation. The results obtained make it possible to improve the dialogue between national and international partners and to provide orientations for the agricultural and rural policy debates. Relying on a methodology that articulated micro-data collection with a macro structural perspective, the program conducted extensive fieldwork to investigate livelihood strategies of rural households, and married the results with a thorough understanding of structural change. The book highlights recurring patterns of diversification and specialization along the process of structural transformation. Further, reconnecting with a broader vision, it emphasizes the difficulties faced by late developers, whose economies offer few alternatives for households to diversify. Based on their assessment, the authors draw a series of policy lessons. They rightly point out the importance of states rebuilding their internal capacities to design comprehensive development strategies. These capacities are critical to addressing major constraints, defining priorities, and ensuring adequate sequencing. Above all, they show that for Sub-Saharan Africa, in the coming two decades, a strong reinvestment in agriculture (in addition to seizing opportunities for the development of manufacturing and services) will be the major policy tool for progressively raising income, mitigating risks, and fostering innovation and rural demand, which constitutes the main engine for rural diversification a major step for structural transformation. The authors also stress the role of the state in provisioning public goods, in adequately and carefully designing incentives, and in using the leverage offered by the development of small towns as a critical mechanism for rural change. These are all sensible and useful reminders for the donor community, governments, and local stakeholders, and represent an important contribution to the role of agriculture for development.